2011
DOI: 10.1093/czoolo/57.1.72
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mate removal on dawn singing behaviour in male pied bush chats

Abstract: To determine the influence of pairing status on dawn singing behaviour in pied bush chats Saxicola caprata, we conducted mate removal experiments across eight territories. The experiment was divided into three stages: pre-removal (pairs were present on their respective territories), removal (females were experimentally removed), and returned (females were released into the focal pairs’ territories). Dawn bout length, song rate, song complexity, percentage performance time, song perch height, and distance of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It therefore still needs to be established for a given species whether longer removal would lead to song rates that are as high as those observed during the dawn chorus. While mate removal affected song rates during the day, in several species it did not affect song rates at dawn (black-capped chickadee [42]; pied bush chat Saxicola caprata [62]; chipping sparrow Spizella passerina [63] ; willow tit Parus montanus [64]; Adelaide's warbler [46]). In these experiments, males had been separated from their mate for the entire night either under natural conditions or when their mate had been experimentally removed.…”
Section: Discussionmentioning
confidence: 99%
“…It therefore still needs to be established for a given species whether longer removal would lead to song rates that are as high as those observed during the dawn chorus. While mate removal affected song rates during the day, in several species it did not affect song rates at dawn (black-capped chickadee [42]; pied bush chat Saxicola caprata [62]; chipping sparrow Spizella passerina [63] ; willow tit Parus montanus [64]; Adelaide's warbler [46]). In these experiments, males had been separated from their mate for the entire night either under natural conditions or when their mate had been experimentally removed.…”
Section: Discussionmentioning
confidence: 99%
“…That is, males used dawn singing to communicate with their close neighbours, to announce and assess their strength or willingness to defend the territory, or to challenge neighbours on a daily basis throughout the breeding season, as reported in social dynamic hypothesis by Staicer et al (1996). Female removal experiment in Pied Bush Chat has also indicated that males direct their dawn chorus to their neighbours instead of their mates (Sethi et al, 2011a). Recent studies have also suggested that birds may use their songs in a more complex or subtle way to interact with specific receivers, particularly in a territorial system where the relationships between territorial neighbours could be mediated by songs used during close-range interaction (McGregor, 1993;Smith, 1997;Todt and Naguib, 2000).…”
Section: Fig 1 Spectrogram Of a 60 Sec Segment Of Dawn Song Bout Ofmentioning
confidence: 99%
“…However, the experimental removal of a mate does not affect the intensity of dawn songs as shown in studies with male pied bush chats ( Saxicola caprata ) (Sethi et al. ) and male chipping sparrows ( Spizella passerina ) (Liu ). Territorial defense is certainly an important function of the dawn chorus of many species.…”
Section: Introductionmentioning
confidence: 97%
“…Social functions vary even within species: for example, attracting, stimulating, and/or guarding mates appear to be important for the dawn chorus of male eastern kingbirds (Tyrannus tyrannus) where the intensity of male dawn singing increases when there is a high abundance of fertile females (Sexton et al 2007), and black-capped chickadees (Poecile atricapillus) where males sang significantly longer following mate removal (Otter & Ratcliffe 1993). However, the experimental removal of a mate does not affect the intensity of dawn songs as shown in studies with male pied bush chats (Saxicola caprata) (Sethi et al 2011) and male chipping sparrows (Spizella passerina) (Liu 2004). Territorial defense is certainly an important function of the dawn chorus of many species.…”
Section: Introductionmentioning
confidence: 97%